Relación entre algunos factores socioculturales con el nivel de calidad del cuidado que brinda la madre adolescente al recién nacido en el Distrito de Moche Enero a Marzo del 2010 - Calderón Sachún, Lía Mabel (2010)
The present study of corelational descriptive type was realised in adolescent mothers and his new born from the district of Moche during the months of January to March of the 2010, in order to determine the existing relation between the sociocultural factors of the adolescent mothers: Level of training, support of the pair, I tie affective (mothers - son), with the taken care quality level of that offers his new born. The sample was constituted by 38 adolescent mothers of the diverse zones of the District of Moche that conformed the universal sample. The used instruments were the format - survey: Sociocultural factors of the Adolescent Mother and the format of observation: Taken care of quality level of that the Adolescent Mother to New born, elaborated by the authors offers considering the dimensions in study and the proposed theoretical frame. The results were reported in graphs with percentage frequencies. In the statistic analysis it was applied the symmetrical measures ordinal by ordinal by means of the Gamma test. Of the analysis of the result one concludes: That the level of training of the adolescent mothers is in its secondary majority of complete (50%); the support of the pair that receives the adolescent mothers mainly is adapted (55,26%); I tie affective (mother - son) of the adolescent mothers is mainly good (63,16%), and the taken care of quality level of that the adolescent mothers offer new born his, is in its good majority (52,63%). Also the analysis of the data I confirm the raised hypothesis, the sociocultural factors: Support, level of training of the pair and I tie affective (mother - son) are related significantly to the taken care of quality level of according to Test Gamma (0,910; 0,987; and 0,895) respectively statistical significance (P = 0,001; P = 0,000; and P = 0,000) respectively.